A case of an accidental miswak injury penetrating the floor of the mouth of a 5-year-old child - Ghada Alqahtani; Irshad Abdulmajeed; Yara AlGoraini (Pediatric Emergency Medicine Journal)
Children often engage in a habit of carrying items in their mouths and are prone to falling. We report a novel case involving a 5-year-old boy who experienced an oral injury characterized by the penetration of “miswak,” a wooden stick used for dental hygiene, into the floor of the mouth and was discharged without complications. Penetrating injuries require a comprehensive evaluation and management. Close monitoring and follow-up are crucial to ensure proper wound healing and resolution of any associated issues.